The transcription factor AmeloD stimulates epithelial cell motility essential for tooth morphology - Chiba, Yuta (J Biol Chem, 2019)
The development of ectodermal organs, such as teeth, requires epithelial–mesenchymal interactions. Basic helix–loop–helix (bHLH) transcription factors regulate various aspects of tissue development, and we have previously identified a bHLH transcription factor, AmeloD, from a tooth germ cDNA library. Here, we provide both in vitro and in vivo evidence that AmeloD is important in tooth development. We created AmeloD-knockout (KO) mice to identify the in vivo functions of AmeloD that are critical for tooth morphogenesis. We found that AmeloD-KO mice developed enamel hypoplasia and small teeth because of increased expression of E-cadherin in inner enamel epithelial (IEE) cells, and it may cause inhibition of the cell migration. We used the CLDE dental epithelial cell line to conduct further mechanistic analyses to determine whether AmeloD overexpression in CLDE cells suppresses E-cadherin expression and promotes cell migration. Knockout of epiprofin (Epfn), another transcription factor required for tooth morphogenesis and development, and analysis of AmeloD expression and deletion revealed that AmeloD also contributed to multiple tooth formation in Epfn-KO mice by promoting the invasion of dental epithelial cells into the mesenchymal region. Thus, AmeloD appears to play an important role in tooth morphogenesis by modulating E-cadherin and dental epithelial–mesenchymal interactions. These findings provide detailed insights into the mechanism of ectodermal organ development.